Association between choroidal thickness and interstitial lung disease in patients with rheumatoid arthritis: A cross-sectional study - Serdar Kaymaz; Nilüfer Savurmuş; Uğur Karasu; Hüseyin Kaya; Furkan Ufuk; Ayşe Rüksan Ütebey; Veli Çobankara; Murat Yiğit (Archives of Rheumatology, 2024)
Objectives: This study aimed to evaluate choroidal thickness (CT) in patients with rheumatoid arthritis (RA) and healthy controls and to determine its relationship with RA-associated interstitial lung disease (RA-ILD). Patients and methods: A total of 63 patients with RA and 36 age- and sex-matched healthy controls were recruited in the cross-sectional study. Serological findings, Disease Activity Score-28, disease duration, and medical treatment of patients were recorded. Patients with RA were subdivided into two groups: patients with RA-ILD (Group 1) and patients with RA but without ILD (RA-noILD; Group 2). CTs were measured using enhanced depth imaging optical coherence tomography. CT was measured at five points: the subfoveal region, 750 μm nasal and temporal to the fovea, 1500 μm nasal and temporal to the fovea. Patients with RA-ILD were evaluated with delta high-resolution computed tomography (ΔHRCT) and pulmonary function test to determine the severity of interstitial lung disease. Results: Four of 63 RA patients were excluded due to comorbidities. Thus, 59 RA patients, 20 in the RA-ILD group and 39 in the RA-noILD group, were included in the analyses. The RA groups were similar in terms of clinical characteristics and laboratory findings. There were statistically significant differences between Group 1, Group 2 and healthy controls (Group 3) compared to all CT values (p<0.05). The mean CT measured at 750 μm and 1500 μm nasal to the fovea was lowest in the RA-ILD group, followed by the RA-noILD and healthy groups (p<0.05). CT measurements did not correlate with the pulmonary function test and ΔHRCT. Conclusion: RA-ILD patients had a thinner CT measured at nasal points. However, there was no association between CT measurements and the severity of ILD.